The Urgency of Public Attitudes of Online Session Rules Implementation in Criminal Cases during COVID-19 Pandemic - Nikmah Fitriah; Muhammad Arief Wijaksono; Maulida Rahmah (Journal of Social Science, 2022)
The background of the research entitled "The Urgency of Public Attitudes on the Application of Online Session Rules in Criminal Cases during the Covid-19 Pandemic" is a phenomenon in society that tends to reject policies from the government, including policies related to handling Covid-19, namely large-scale social restrictions policies. . That's why this study aims to find out how the public's attitude in responding to state provisions that stipulate online criminal case trials both as the general public and defendants in criminal cases in particular. The type of research used is a sociological normative type of research, which is to examine the problem of implementing various regulations in society. The results of this study are (1). In general, the attitude of the community towards the government's policy of restricting activities in public places or facilities is that they do not comply and take them seriously. (2). The attitude of the accused towards the holding of online criminal cases shows that more people respond positively than negatively. The comparison is 8 positive response items (53.3%).